2012
DOI: 10.1007/s11250-012-0110-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibodies to peste des petits ruminants virus before and during outbreaks of the disease in Awash Fentale district, Afar, Ethiopia

Abstract: The present study was conducted to assess the seroprevalence of peste des petits ruminants (PPR) in sheep and goats in Awash Fentale district, Afar, Ethiopia. Small ruminants in the district had poor herd immunity at the first visit and succumb to the disease then after. The seroprevalence during the time of an outbreak was much higher compared with the initial levels: 7.3% and 42.6% in sheep and goats, respectively. The higher seroprevalence figure in goats was suggestive of their relative susceptibility to P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 8 publications
2
21
0
Order By: Relevance
“…Our model, in accordance with these findings, identified the eastern Amhara as at high risk of PPR occurrence (Figure 2). Moreover, high seroprevalence of PPRV in small ruminants was reported in neighboring lowland pastoral areas (11,18,51,52), identified at medium risk by our model. According to our model, highlands are at higher risk for PPR outbreaks than adjacent areas (Figure 2), which seems in apparent contradiction with the cited serosurveys.…”
Section: Discussionmentioning
confidence: 61%
“…Our model, in accordance with these findings, identified the eastern Amhara as at high risk of PPR occurrence (Figure 2). Moreover, high seroprevalence of PPRV in small ruminants was reported in neighboring lowland pastoral areas (11,18,51,52), identified at medium risk by our model. According to our model, highlands are at higher risk for PPR outbreaks than adjacent areas (Figure 2), which seems in apparent contradiction with the cited serosurveys.…”
Section: Discussionmentioning
confidence: 61%
“…According to some reports, in mixed populations, the serological prevalence rate has been found to be higher in sheep than in goats, which is attributed by the higher survival rate in sheep [8,194,195]. In contrast, some studies have reported that goats are more susceptible than sheep, and therefore have a higher probability of developing PPRV antibodies [196,197,198]. Interestingly, epidemiological surveillance studies carried out in different enzootic regions have revealed PPRV seroprevalence in other ruminants including cattle, buffalo and camel [194,195].…”
Section: Host Susceptibility and Resistance To Pprmentioning
confidence: 99%
“…Goats have been found to be more susceptible with severe form of clinical disease than sheep (Lefevre and Diallo, 1990; Nanda et al, 1996; Dhar et al, 2002; Singh et al, 2004a; Delil et al, 2012; Truong et al, 2014). It has also been observed that the rate of recovery is lower in goats than in sheep (Singh et al, 2004a).…”
Section: Introductionmentioning
confidence: 99%